Transportation policy formation in Detroit 1945-1985 - Neill, William J. V. (1986)
The thesis traces the development of transportation policy formation at regional and local levels of government in the Detroit region since 1945. Three postwar transportation policy climates are identified. The first, to the early sixties, was marked by a reasonable degree of regional consensus on freeways as the basis of regional transportation policy. The second, covering the period to the 1970's, saw this consensus begin to break down. The subsequent period to the present has been marked by an almost total collapse in regional consensus on transportation policy. Within the maintenance of a sensitivity to the dangers inherent in structuralist Marxist theorizing, the hypothesis is explored that class relationships have been of primary influence in accounting for this "macro dynamic" of transportation policy formation. The role of physical planners and implications for planning theory is a particular focus of study. The research concludes that, at a time when "grand" Marxist theorizing is coming under criticism, the primacy of class relationships as an explanatory variable can be sustained in the case of Detroit but in terms of the development of a more adequate theory of planning the research points to the need for supplemental theory construction on the discretion and influence of planners within the class pattern (as opposed to determination) of events.